2018
DOI: 10.1155/2018/8187457
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Emotional Expression in Frontotemporal Dementia: A Pilot Study

Abstract: Objective Although emotional blunting is a core feature of behavioral variant frontotemporal dementia (bvFTD), there are no practical clinical measures of emotional expression for the early diagnosis of bvFTD. Method Three age-matched groups (bvFTD, Alzheimer's disease (AD), and healthy controls (HC)) of eight participants each were presented with real-life vignettes varying in emotional intensity (high versus low) with either negative or positive outcomes. This study evaluated verbal (self-reports of distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Fourteen studies explored emotional processing and empathy. Eleven studies (79%) reported a greater deficit in individuals with bvFTD compared with patients with AD (Kipps et al, 2009a ; Buhl et al, 2013 ; Bertoux et al, 2015 ; Chiu et al, 2016 ; Dermody et al, 2016 ; Carr et al, 2017 , 2018 ; Fong et al, 2017a ; Sturm et al, 2017 , 2018 ; Dodich et al, 2018 ), and the other three studies specifically observed reduced levels of empathy indicators in patients with bvFTD. The remaining studies did not report significant differences between the two groups of patients (Fernandez-Duque et al, 2010 ; Reul et al, 2017 ; Synn et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies explored emotional processing and empathy. Eleven studies (79%) reported a greater deficit in individuals with bvFTD compared with patients with AD (Kipps et al, 2009a ; Buhl et al, 2013 ; Bertoux et al, 2015 ; Chiu et al, 2016 ; Dermody et al, 2016 ; Carr et al, 2017 , 2018 ; Fong et al, 2017a ; Sturm et al, 2017 , 2018 ; Dodich et al, 2018 ), and the other three studies specifically observed reduced levels of empathy indicators in patients with bvFTD. The remaining studies did not report significant differences between the two groups of patients (Fernandez-Duque et al, 2010 ; Reul et al, 2017 ; Synn et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Emotion responding is also disturbed, with patients showing a diminished self-conscious emotional behavior (embarrassment and amusement) as well as a diminished associated physiological response, particularly toward negative emotional stimuli (239, 240). Similarly, blunted expressiveness in response to emotional stimuli, especially in low-intensity context and decreased autonomic responses such as skin conductance have been observed in bvFTD (241244). Finally, recent investigations have showed that patients with bvFTD could have difficulties to imitate facial emotion expressions (245).…”
Section: Promising Cognitive and Psychological Markers For Bvftd Beyomentioning
confidence: 84%
“…Patients with FTD may have apathy, which is one of the most common and disabling dementia syndromes (Fernández-Matarrubia et al, 2018). These patients now require greater intensity of emotional stimuli to provoke suffering and emotional expression when compared to healthy people (Carr et al, 2018). However, in the early phase of the disease, other manifestations may be present, such as disinhibition, which will determine the course of the disease and the anatomical changes developed (Santamaria-Garcia et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…While sexual hypofunction is related to atrophy of the right supramarginal gyrus, middle frontal gyrus, and thalamus, sexual hyperfunction is associated with cerebellar atrophy (Ahmed et al, 2018). One of the differences between the apathy of AD with FTD is that in the former there are no anatomical changes, while in the latter there is atrophy of the anterior cingulate cortex, ventromedial prefrontal cortex and anterior temporal lobes (Carr et al, 2018). .…”
Section: Resultsmentioning
confidence: 99%